A Novel Iterative Method for Solving Systems of Fractional Differential Equations. (30th July 2013) - Hesameddini, E.; Rahimi, A.
Abstract : The Reconstruction of Variational Iteration Method (RVIM) technique has been successfully applied to obtain solutions for systems of nonlinear fractional differential equations: D ∗ α x i ( t ) = N i ( t, x 1, …, x n ), x i ( k ) = c k i, 0 ≤ k ≤ [ α i ], 1 ≤ i ≤ n, where D ∗ α denote Caputo fractional derivative. The RVIM, for differential equations of integer order is extended to derive approximate analytical solutions for systems of fractional differential equations. Advantage of the RVIM, is simplicity of the computations and convergent successive approximations without any restrictive assumptions or transform functions. Some illustrative examples are given to show the validity of this method for solving linear and nonlinear systems of fractional differential equations.